Comparative qualitative assessment of DAG production from medium chain fatty acids mediated by enzymatic and chemical catalysts under individually optimized conditions. (November 2019) - Das, Kankana; Ghosh, Mahua
Abstract: The present study was aimed to assess the production attributes of synthesizing structured diacylglycerols from bioactive medium chain fatty acids in a stirred tank reactor by known methods of catalysis i.e. enzymatic and chemical on a comparative basis. Enzymatic esterification was performed using two commercially available immobilized lipases viz. Rhizomucor meihei and Candida antarctica, whereas, chemical was carried out using concentrated sulphuric acid (H2 SO4 ) as acid catalyst. Two different medium chain fatty acids caprylic (C8:0 ), capric (C10:0 ) along with glycerol were used as the substrates for the esterification process. Reaction parameters, such as substrate molar ratio, time of reaction and acid values were standardized in the stirred tank reactor, keeping the catalyst (enzyme and chemical) concentration and reaction temperature constant. Chromatographic techniques were employed to monitor and separate the different isomers. Structured diacylglycerol yields of about 58.86 ± 4.05% and 53.77 ± 3.74% were obtained with C8:0 -RMIM and C8:0 -NS435 enzyme at 18th and 6 th hr respectively. About 55.41 ± 3.95%, 51.89 ± 2.60% significant yields were also obtained in case of C10:0 - RMIM and NS435 enzymes at 18th and 6th h respectively. The study showed better eco-friendly qualitative yield of DAG production can be achieved with biological catalysts as compared to chemical catalysts.